2016
DOI: 10.1039/c6ta06497c
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced degradation of methylammonium lead triiodide perovskite semiconductors

Abstract: Photoinduced degradation is a critical obstacle for the real application of novel semiconductors for photovoltaic applications. In this paper, the photoinduced degradation of CH 3 to its role in creating ion vacancies. The degradation in air suggests that both oxygen and water contribute to the fast photodecomposition of CH 3 NH 3 PbI 3 into lead salts rather than water alone. Given these basic yet fundamental understandings, the design of hydrophobic capping layers becomes one prerequisite towards long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 37 publications
9
108
2
Order By: Relevance
“…The combination of reduced grain size throughout the film and a higher defect density serve as the cause for a lower fill factor (FF) and short-circuit current density (J SC ) in sol-eng devices, resulting in a lower overall efficiency. [18,20,48] This observation and our measurements of the local temperature demonstrate that light induced heating effects alone do not result in a degradation of the perovskite film on this timescale and the observed degradation is a consequence of exposure to light and oxygen. [42,45,46] For the PbAc 2 recipe, the inherent water in the precursor solution as well as the addition of hypophosphorous acid results in an enlargement of the grain size and improved film morphology resulting in perovskite films with high electronic quality and low defect density.…”
Section: Photovoltaic Performancesupporting
confidence: 57%
“…The combination of reduced grain size throughout the film and a higher defect density serve as the cause for a lower fill factor (FF) and short-circuit current density (J SC ) in sol-eng devices, resulting in a lower overall efficiency. [18,20,48] This observation and our measurements of the local temperature demonstrate that light induced heating effects alone do not result in a degradation of the perovskite film on this timescale and the observed degradation is a consequence of exposure to light and oxygen. [42,45,46] For the PbAc 2 recipe, the inherent water in the precursor solution as well as the addition of hypophosphorous acid results in an enlargement of the grain size and improved film morphology resulting in perovskite films with high electronic quality and low defect density.…”
Section: Photovoltaic Performancesupporting
confidence: 57%
“…Several groups observed significant photoinstabilities of MAPbI 3 . However, most experiments were performed in air.…”
Section: Perovskite Degradationmentioning
confidence: 94%
“…Using x-ray photoelectron spectroscopy (XPS), we observed no significant traces of oxygen (O 1s) in the PTEAI-capped film, even after 640 minutes of accelerated aging tests (Figure 5b), revealing that the PTEAI-capped MAPbI3 inhibits the formation of an oxygen-containing compounds, 51 and increases film stability. In contrast, we found that the amount of oxygencontaining compounds 51 in bare MAPbI3 increases within 460 minutes, which can be attributed to a PbOx compound. 51,52 The presence of the oxygen in fresh bare MAPbI3 indicating surface contamination from atmospheric oxygen is significantly higher than in fresh PTEAI-capped samples.…”
Section: Protection Mechanisms In Top-performing Candidatesmentioning
confidence: 99%